Sentiment classification on Bengali food and restaurant reviews - Hossain, Abid; Sajin, Tanjim Hussain; Bhuiyan, Md Hasibuzzaman; Khan, Farhan Akbor; Anka, Sankalpa (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2024.